Ethics, law, and military operations - Whetham, David (Palgrave Macmillan, 2011)
While there are many legal textbooks on the laws of armed conflict and academic works on ethical issues in international relations, this is the first text on the relevance of legal and normative issues in military practice. It covers the entire spectrum of military operations and is written with military decision-makers particularly in mind.